2010
DOI: 10.1186/1471-2164-11-319
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression links the electron transfer pathway of Shewanella oneidensis to chemotaxis

Abstract: BackgroundBy coupling the oxidation of organic substrates to a broad range of terminal electron acceptors (such as nitrate, metals and radionuclides), Shewanella oneidensis MR-1 has the ability to produce current in microbial fuel cells (MFCs). omcA, mtrA, omcB (also known as mtrC), mtrB, and gspF are some known genes of S. oneidensis MR-1 that participate in the process of electron transfer. How does the cell coordinate the expression of these genes? To shed light on this problem, we obtain the gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The final destination for electrons prior to reduction of iron oxides is MtrC. In 2010, Tai et al (2010) assessed potential networks of transcriptional regulation between chemotactic and electron transport properties and found that previously unknown roles of genes including cheA (a chemotaxis gene), mgtE-1 (an Mg 2þ transport gene) and SO4572 (a triheme cytochrome gene). Similar to the discovered mechanism of proton pumping in the F 1 F 0 -ATP synthase using bacteriorhodopsin in membrane vesicles, scientists have proven that the protein complex of MtrCAB conducts electron when embedded within membrane vesicles (Hartshorne et al, 2009).…”
Section: Cytochromes (Cell-bound)mentioning
confidence: 99%
“…The final destination for electrons prior to reduction of iron oxides is MtrC. In 2010, Tai et al (2010) assessed potential networks of transcriptional regulation between chemotactic and electron transport properties and found that previously unknown roles of genes including cheA (a chemotaxis gene), mgtE-1 (an Mg 2þ transport gene) and SO4572 (a triheme cytochrome gene). Similar to the discovered mechanism of proton pumping in the F 1 F 0 -ATP synthase using bacteriorhodopsin in membrane vesicles, scientists have proven that the protein complex of MtrCAB conducts electron when embedded within membrane vesicles (Hartshorne et al, 2009).…”
Section: Cytochromes (Cell-bound)mentioning
confidence: 99%
“…In addition, highly co-expressed genes may be involved in the same biological process or metabolic pathway [ 15 , 16 ], but the expression profiles of most genes in the same pathway are often uncorrelated [ 17 ]. Recent studies have demonstrated that the co-regulation pattern of two genes is affected by the expression levels of third genes or genetic variations in yeast and humans [ 18 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multi-group time-course study on ageing [ 13 ] has identified gene sets whose co-expression is modulated by ageing. Application on data of Shewanella oneidens identified a network of transcriptional regulatory relationships between chemotaxis and electron transfer pathways [ 14 ]. Many other studies have also shown the significant utility of application of differential co-expression analysis [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%